Designing self-crosslinkable ternary blends using epoxidized natural rubber (ENR)/poly(ethylene-co-acrylic acid)(EAA)/poly(ε-caprolactone) (PCL) demonstrating triple-shape memory behavior. (5th June 2021) - Kim, Jae-Chul; Chang, Young-Wook; Sabzi, Mohammad
Graphical abstract: Highlights: A facile route to prepare triple shape memory polymer based on self-crosslinkable ternary blends w as developed. The ternary blends can form chemically crosslinked networks via interchain reaction between reactive groups of component polymers. The self-crosslinked polymer blends have two distinct crystalline melting transitions. Abstract: The aim of this work is developing a facile and versatile route for preparing chemically crosslinked triple-shape memory polymers (SMPs). Hence, epoxidized natural rubber(ENR)/poly(ethylene-co-acrylic acid)(EAA)/poly(ε-caprolactone) (PCL) ternary blends were fabricated using the facile melt-mixing method. Interestingly, it was observed that the resultant ternary blends could self-crosslink during molding at high temperature without need for any crosslinking agents. Differential scanning calorimeter (DSC) and dynamic mechanical analyzer (DMA) analyses revealed that all of the ternary blends have two well-separated thermal transitions (Tm, PCL and Tm, EAA ) and, as a result, they exhibited triple-SM behavior. Moreover, the mechanical properties as well as shape memory effect of ternary blends were improved with carboxylation of PCL. The developed ternary blends can be considered as a promising SM material in many in-vivo and aerospace applications.